Self-Leadership dan Kepatuhan Cuci Tangan: Membangun Budaya Hygiene dari dalam Diri Perawat - Ayu, Windri Dewi; Jaelani, Ahmad; Abdillah, Awaludin Jahid (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aimed to determine the relationship between self-leadership and hand hygiene compliance among nurses. A quantitative correlational design was used. The results showed that 54.5% of nurses had high self-leadership, but only 29.5% adhered to hand hygiene procedures. A chi-square test showed a significant relationship between self-leadership and compliance (χ² = 7.453; p = 0.006). Conclusion: Better compliance is associated with better self-leadership, but low compliance indicates differences in behavioral intentions. Therefore, to improve patient safety culture, self-leadership training combined with organizational support is needed. Keywords: Hand Hygiene Compliance, Patient Safety, Nurses, Self-Leadership